KEBERAGAMAN GEN KUCING PEAKNOSE PERSIA DAN MUNCHKIN NON STANDART PEROLEHAN PERKAWINAN DAN PERILAKU HARIAN KUCING DENGAN MANUSIA - Galuh Dwi Purwasih (JIK-PkM: Jurnal Inovatif dan Kreatif hasil Pengabdian kepada Masyarakat, 2023)
The research entitled the diversity of behavior of non-standard Persian peaknose cats and munchkins in the acquisition of cross-breeding is a further study by presenting the extent to which the behavior patterns of non-standard Persian and munchkin cats (NS). The Persian peaknose cat is very popular in Indonesia and many have kept it as a pet, its appearance is cute and adorable, at first glance it looks like a doll, its fur is long and dense and its body is large, its face is round, its nose is short or pug while the Munchkin NS cat has the shape of a cat which is the same as cats in general but has short legs so it looks midget. However, this NS cat can give birth to all of her children with short legs or some of them can have short legs or all of them can have long legs but they still carry the gene for short legs. This research is a case study in an exploratory manner presented qualitatively. Sampling of cats was screened based on a minimum age of 1 to 1.5 years and collected by random sampling munchkin NS 4 peaknose persian 4 tails. Observation of sample morphology based on mating path, recording of morphological characters (color body, color pattern, and tail length) were analyzed using calculations for dominant, recessive genes or relationships and concluded qualitatively, the frequency of gene presence was determined for each of the 4 gene loci, namely: persian peaknose w-W; A A; and munchkin NS D-d: s-S gene behavior of Persian peaknose cat breeds and munchkin NS which were observed to have random diversity, and did not show any other gene dominance. This also aims to observe the behavior of Persian peaknose cats and munchkin NS, their reproductive organs can occur randomly generative or vegetative.